Analisis Kinerja Koperasi Serba Usaha (Ksu) â€œTri Dwi Ekaâ€ Menggunakan Metode Balanced Scorecard - Pasek, Gede Widiadnyana; Arta, Komang Dyas Upayana; Kasih, Ni Luh Sri (Universitas Pendidikan Ganesha, 2020)
The purpose of this research is to analyze the performance of Tri Dwi Eka KSU using the Balanced Scorecard Method. This research is a descriptive quantitative research. Based on the results of the analysis, it shows that the company's health uses the Balanced Scorecard Method. Based on the theory and provisions of the KUKM regulation no. 20 / Per / M.KUKM / XI / 2008, namely from a financial perspective starting from the ratio of own capital, efficiency, liquidity, asset profitability, capital profitability itself can be categorized as healthy in accordance with the stipulated provisions. Assessment from a customer perspective as measured by customer acquisition and customer rent can be categorized as healthy because the greater the customer perspective, the better the health level of the company's performance. Assessment from the internal business perspective process as measured by SCE, standard time divided by the time of completion can be categorized as healthy as well. Assessment of company performance is seen from the perspective of learning and growth, which from the level of employee productivity and employee retention can be categorized as healthy